MSCs interaction with the host lung microenvironment: An overlooked aspect? - Weiss, Daniel J.; Rolandsson Enes, Sara (Frontiers in Immunology, 2022)
Mesenchymal stromal cells (MSCs) were identified more than 50 years ago, and research advances have promoted the translation of pre-clinical studies into clinical settings in several diseases. However, we are only starting to uncover the local factors that regulate cell phenotype, cell function, and cell viability across tissues following administration in different diseases. Advances in pre-clinical and translational studies suggest that the host environment, especially inflammatory active environments, plays a significant role in directing the infused MSCs towards different phenotypes with different functions. This can significantly effect their therapeutic efficacy. One way to study this interaction between the host environment and the infused cells is to expose MSCs ex vivo to patient samples such as serum or bronchoalveolar lavage fluid. Using this approach, it has been demonstrated that MSCs are very sensitive to different host factors such as pathogens, inflammatory cytokines, and extra cellular matrix properties. By understanding how different local host factors effect MSC function it will open possibilities to select specific patient sub-groups that are more likely to respond to this type of treatment and will also open possibilities to prime the local host environment to increase viability and to enrich for a specific MSC phenotype. Here, we aim to review the current understanding of the interaction of MSCs with the host microenvironment. To narrow the scope of this mini review, the focus will be on the pulmonary microenvironment, with a specific focus on the diseases acute respiratory distress syndrome (ARDS) and cystic fibrosis (CF).